2021
DOI: 10.1080/02688697.2020.1868404
|View full text |Cite
|
Sign up to set email alerts
|

The economic and psychological impact of cancellations of elective spinal surgeries in the COVID-19 era

Abstract: Background: The adoption of health care restrictions due to the COVID-19 pandemic led to the cancellation of elective surgical care. However, the impact on patients is unknown. Objective: To evaluate the psychological and economic impact of the cancellation of scheduled spinal operations. Methods: We identified 50 patients with cancelled surgeries between 16 March 2020 and 24 April 2020. Forty-nine (98%) participants were contacted, with whom the modified WES-Pi questionnaire was filled in during a telephone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although these conditions are not life-threatening, delayed treatment can influence definite loss of functionality23 and increase indirect costs related to work absenteeism. Consequently, psychological symptoms, such as anger and sadness, and the economic impact due to surgical cancellation of elective surgeries have also been documented 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these conditions are not life-threatening, delayed treatment can influence definite loss of functionality23 and increase indirect costs related to work absenteeism. Consequently, psychological symptoms, such as anger and sadness, and the economic impact due to surgical cancellation of elective surgeries have also been documented 24…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, psychological symptoms, such as anger and sadness, and the economic impact due to surgical cancellation of elective surgeries have also been documented. 24 On the other hand, clinical deterioration was even more frequently observed in patients with functional (39.5%) or CSF disorders (40%). These subgroups of patients can be considered more vulnerable to becoming critically ill if they become infected, but treatment on time can reduce mortality and the need for residential nursing care.…”
Section: Open Accessmentioning
confidence: 97%
“…who also found disappointment to be the most common emotional reaction by patients who had their elective spinal surgical procedures cancelled because of the Covid-19 pandemic. 14…”
Section: Discussionmentioning
confidence: 99%
“…Although the anxiety induced by this pandemic on healthcare workers is well documented, the true effect upon patients is poorly understood, with only three studies published in the literature so far that have directly explored the impact on patients of delayed elective surgical procedures. 1114…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies published over the years appear to suggest either a stasis or a significant deterioration in the quality of life, even for waiting periods of less than 3 months [ 5 , 6 ]. A number of observational studies conducted during the pandemic confirmed a loss of health or quality of life due to a postponement of elective surgery procedures (e.g., [ 7 9 ]). Cancellations were reported to have negative consequences in terms of pain, work productivity, or psychological status.…”
Section: Introductionmentioning
confidence: 99%